Molecular pathways of generation and detoxification of reactive oxygen species and induction of apoptosis in yeasts - Sidra Gull; Chaudhry Ahmed Shabbir; Zaman Khan; Dilara A. Bukhari; Abdul Rehman (Arabian Journal of Chemistry)
Reactive oxygen species (ROS) can trigger cell death in Saccharomyces cerevisiae and other lower eukaryotic organisms. Protein structure and function may be altered by ROS produced by cellular metabolism or by exposure to environmental oxidants. This happens regardless of whether peroxidases, superoxide dismutases, or catalases are active. Depending on the redox state of cysteine residues, oxidative alteration of sulfhydryl groups in proteins may inhibit protein activity or begin alternative pathways that affect cell function. Redox control is made possible by conserved, interdependent thioredoxin and glutaredoxin systems, which may play a comparable function in metal homeostasis in eukaryotic organisms. In response to oxidative stress, gene expression in S. cerevisiae is regulated by several transcription factors, including Yap1, and Gpx3 peroxidase, and one function of Yap1 is to regulate gene expression. Notwithstanding this information, many issues about the link between ROS production and apoptosis remain unsolved. ROS may disrupt cells or activate certain molecular and cellular pathways during cell death, promoting apoptosis. This review aims to elucidate ROS’s essence, their harm to cells, how S. cerevisiae reacts to ROS, and how ROS might affect cell integrity and cause cell death.